Intracerebral Hemorrhage Hemisfer Dextra: A Case Report - Fitriyani, Fitriyani; Sephia, Elmarossa Dinda (Medula, 2024)
Intracerebral hemorrhage is a brain injury due to acute extravasation of blood into the brain parenchyma with or without expansion of blood into the ventricles due to rupture of blood vessels. Several factors that increase the risk of this condition are chronic hypertension, amyloid angiopathy, anticoagulant treatment, and vascular malformations. Intracerebral hemorrhage can cause primary and secondary brain injury. Primary brain injury is the initial damage to the parenchyma by a blood clot. While secondary brain injury is a pathological change after bleeding. The most common clinical sign of this disease is a sudden focal neurological deficit. Management of intracerebral hemorrhage starts from drug therapy to surgery. This article discusses the case of a 43-year-old male patient with complaints of weakness in the left leg and arm since 3 hours before admission to the hospital. Other complaints include sudden vomiting preceded by a severe headache 1 day before admission to the hospital. The patient has a history of hypertension since 13 years ago but rarely consumes drugs and heart disease (STEMI) in June 2024. The patient also has a smoking habit since 10 years ago. Physical examination found blood pressure 165/97 mmHg, mouth turned to the left (N VII), tongue deviation to the left (N XII), left hemiparesis. Sodium examination found 133 mmol / L (hyponatremia). Non-contrast head CT scan examination found the impression of a hyperdense lesion in the right hemisphere, an impression of intracerebral hemorrhage. The patient was given drug management without surgical management.